EFFICACY OF PRIMARY REPAIR IN TERMS OF FREQUENCY OF INTRAABDOMINAL ABSCESS IN PATIENTS OF NONDESTRUCTIVE COLONIC INJURIES WITH COLOSTOMY - Sajid Rehman Randhawa; Khurram Saqib (Journal of University Medical & Dental College, 2013)
ABSTRACT Objective: To compare the efficacy of primary repair in terms of frequency of intra-abdominal abscess in patients of nondestructive colonic injuries with colostomy. Study Design: Randomized clinical trial. Setting: Surgical unit IV DHQ/Allied Hospital Faisalabad; from January 2012 to June 2013. Subjects: 62 patients with colonic injuries, 31 patients in each group. Method: Sixty two cases presenting with colonic trauma were studied to know the risk of post operative complication in terms of frequency of intra abdominal abscess. There were 31 patients in each group. Half of patients who underwent primary repair for colonic injuries fall in group A and half of patients who underwent colostomy fall in group B. Results: Primary repair was done in patients of group A & colostomy was done in group B. The hospital stay ranged from 14 to 21 days. In the data, frequency of intra abdominal abscess was calculated within 2 weeks post operatively in each group. In total 62 patients, there were 3 (4.84%) patients who developed intra abdominal abscess, 1 patient in group A (3.22%) and 2 patients (6.45%) in group B. The primary repair did not show an increase in intra-abdominal sepsis, regardless of risk factors (the number of associated injuries, the level of fecal contamination, and transfusion volume). Conclusion: Primary repair of penetrating colonic injuries is safe and effective. It prevents the patient from unnecessary repeated hospitalization, complications of colostomy, and the economic and psychological trauma associated with stoma formation.